(3OjhGf GHf NWjH OGQjGs - (3eMeO Hf CMeO Hf SdjeGf Hf jYbhH GdCfUGQj GdNRQLj, GdOeTbj GdHjSGfj ; GHf GdNWjH OGQjG,J (B810 (3g` s
(3ChdgG (B:s
(3bGd TjNfG GdTgjQ HGHf NWjH OGQjG (B: (3CMeOc Gddge Ydi fYe CbdgG dOi fXe GdbQjV hChd bUGFO GdOjhGf (B: s
(3BNQgG (B:s
(3ef cdGe cJHg Ydi bUGFO fHhjg fXegG GdTjN TeS GdOjf CHh GdeYGdi eMeO Hf eMeO GdeUQi (B: (3Gddge CeJfG eSdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B266s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(225(3b(B) s
Keywords: (3GdCOHs